2023
DOI: 10.1093/ehjcr/ytae014
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiography-guided balloon-assisted percutaneous closure of a large secundum atrial septal defect in a pregnant woman: a case report

Radityo Prakoso,
Rina Ariani,
Brian Mendel
et al.

Abstract: Structured Abstract Background According to 2018 European Society of Cardiology (ESC) guidelines, atrial septal defect (ASD) closure can be performed during pregnancy but is rarely indicated. In this case, we demonstrate the viability of percutaneous balloon-assisted ASD closure without fluoroscopy in a pregnant woman. Case summary A 23-year-old G3P2A0 woman who was 20 weeks pregnant had prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[1][2][3] Recent studies have demonstrated favorable outcomes with device closure of acyanotic CHDs, including atrial septal defect (ASD), ventricular septal defect (VSD), and patent ductus arteriosus (PDA). [4][5][6][7] Concerns over radiation exposure, especially in children and pregnant women, have led to the adoption of non-fluoroscopy techniques for defect closure, with comparable efficacy and safety to traditional methods. In our effort to mitigate radiation exposure during transcatheter closure procedures for congenital heart defects, we have implemented a policy promoting non-fluoroscopy techniques, even in challenging cases such as multiple ventricular septal defects (VSDs) and in pregnant women with atrial septal defect (ASD) with pulmonary hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Recent studies have demonstrated favorable outcomes with device closure of acyanotic CHDs, including atrial septal defect (ASD), ventricular septal defect (VSD), and patent ductus arteriosus (PDA). [4][5][6][7] Concerns over radiation exposure, especially in children and pregnant women, have led to the adoption of non-fluoroscopy techniques for defect closure, with comparable efficacy and safety to traditional methods. In our effort to mitigate radiation exposure during transcatheter closure procedures for congenital heart defects, we have implemented a policy promoting non-fluoroscopy techniques, even in challenging cases such as multiple ventricular septal defects (VSDs) and in pregnant women with atrial septal defect (ASD) with pulmonary hypertension.…”
mentioning
confidence: 99%
“…In our effort to mitigate radiation exposure during transcatheter closure procedures for congenital heart defects, we have implemented a policy promoting non-fluoroscopy techniques, even in challenging cases such as multiple ventricular septal defects (VSDs) and in pregnant women with atrial septal defect (ASD) with pulmonary hypertension. 4,5 This strategic shift aims to minimize the potential risks associated with radiation exposure, particularly for vulnerable populations. In one study demonstrated by Siagian et al 6 , echocardiography-guided closure of patent ductus arteriosus (PDA) is a viable alternative to fluoroscopyguided procedures.…”
mentioning
confidence: 99%